2015
DOI: 10.1038/srep13588
|View full text |Cite
|
Sign up to set email alerts
|

FABP4 reversed the regulation of leptin on mitochondrial fatty acid oxidation in mice adipocytes

Abstract: Fatty acid binding protein 4 (FABP4), plays key role in fatty acid transportation and oxidation, and increases with leptin synergistically during adipose inflammation process. However, the regulation mechanism between FABP4 and leptin on mitochondrial fatty acid oxidation remains unclear. In this study, we found that FABP4 reduced the expression of leptin, CPT-1 and AOX1 in mice adipocytes. Conversely, FABP4 was down-regulated in a time-dependent manner by leptin treatment. Additionally, forced expression of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…In brief, adipose tissues was homogenized in sucrose/Tris/EDTA buffer, and incubated for 60 min in the reaction mixture which contained [1- 14 C] palmitic acid and measured for trapped CO 2 . For in vivo study of palmitate oxidation to CO 2 , we used the modified method from Sebastián and our pervious study5556. For the trapped radioactive CO 2 measurement, a parafilm-sealed system was used.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, adipose tissues was homogenized in sucrose/Tris/EDTA buffer, and incubated for 60 min in the reaction mixture which contained [1- 14 C] palmitic acid and measured for trapped CO 2 . For in vivo study of palmitate oxidation to CO 2 , we used the modified method from Sebastián and our pervious study5556. For the trapped radioactive CO 2 measurement, a parafilm-sealed system was used.…”
Section: Methodsmentioning
confidence: 99%
“…FABP4, identified as a cytosolic protein, is strongly up-regulated during differentiation of preadipocytes into adipocytes [21, 38]. Here, we first determined that Hoxa5 acts as a transcriptional activator of the key adipogenic factor-Fabp4.…”
Section: Discussionmentioning
confidence: 99%
“…The X-treme GENE HP Reagent (Roche, Switzerland) was used in plasmids transfection. The transfection procedure was as described in our previous reports in detail [21]. …”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that knockout mice with null Fabp4 expression had an increase of EAT mass [42]. Moreover, the fatty acids solubility could trigger other routes that are related with the Lep role [43].…”
Section: Discussionmentioning
confidence: 99%